Late Quaternary population expansion in gray brocket deer [ Subulo gouazoubira (G. Fisher, 1814), Cervidae, Mammalia] in Brazil - Alex Hubbe; Mark Hubbe; Elver Luiz Mayer; Eliane Nunes Chim; Paulo Miguel Haddad‐Martim; Augusto S. Auler; Luís B. Piló; William J. Pestle; Alba Rey‐Iglesia; Isac dos Santos Antônio Machado; Paulo C. F. Giannini; Eluzai Dinai Pinto Sandoval; et al. (Journal of Quaternary Science, 2025)
There is little information about the changes in the abundance of mammalian species in South America during the late Quaternary, which is a key parameter to understanding past ecological and evolutionary dynamics. Here, we describe a conspicuous increase in the abundance of the gray brocket deer ( Subulo gouazoubira G. Fisher, 1814; Mammalia) during the late Quaternary in Brazil based on paleontological evidence. We studied the material retrieved from pitfall deposits in Cuvieri Cave (Brazil) representing three time intervals (Late Pleistocene, Pleistocene/Holocene transition, and Holocene). The deposits in this cave were previously characterized in terms of facies composition, chronology, and overall taxa and taphonomy. We combined previous data with taxonomic identification at the species level for deer (morphological and ancient DNA analyses), quantification of the number of individuals for large mammals (>10 kg), taphonomic analyses, and stratigraphic distribution of specimens. Our results show that while in the Late Pleistocene gray brocket deer corresponded to up to 18% of 38 individuals, in the Holocene they represented at least 82% of 78 individuals. We interpret this change in frequency as a considerable increase in abundance in the surroundings of the cave, after excluding major taphonomical biases. The causes for this phenomenon are uncertain but could have involved a surplus of food availability and predation release due to the late Quaternary extinction event.

Dating the ebb and flow of Tiwanaku and post-collapse material culture across the Andes - Erik J. Marsh; Bruce Owen; Antti Korpisaari; Nicola Sharratt; Paul Goldstein; Ben Vining; Sarah Baitzel; Susan deFrance; Mark Hubbe; Santiago Ancapichún (Quaternary International, 2025)

Modules and Mosaics in the Evolution of the Tetonius – Pseudotetonius Dentition - Naava H. Schottenstein; Mark Hubbe; John Hunter (Journal of Mammalian Evolution, 2020)

Eating out or dining in: modeling diverse dietary strategies in the Middle Period, San Pedro de Atacama, Chile - William J. Pestle; Christina Torres-Rouff; Mark Hubbe; Erin K. Smith (Archaeological and Anthropological Sciences, 2017)